Management of neck metastases in head and neck cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Paleri, V; Urbano, T G; Mehanna, H; Repanos, C; Lancaster, J; Roques, T; Patel, M; Sen, M
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. A rational plan to manage the neck is necessary for all head and neck primaries. With the emergence of new level 1 evidence across several domains of neck metastases, this guideline will identify the evidence-based recommendations for management. Recommendations: Computed tomographic or magnetic resonance imaging is mandatory for staging neck disease, with choice of modality dependant on imaging modality used for the primary site, local availability and expertise. (R) Patients with a clinically N0 neck, with more than 15–20 per cent risk of occult nodal metastases, should be offered prophylactic treatment of the neck. (R) The treatment choice of for the N0 and N+ neck should be guided by the treatment to the primary site. (G) If observation is planned for the N0 neck, this should be supplemented by regular ultrasonograms to ensure early detection. (R) All patients with T1 and T2 oral cavity cancer and N0 neck should receive prophylactic neck treatment. (R) Selective neck dissection (SND) is as effective as modified radical neck dissection for controlling regional disease in N0 necks for all primary sites. (R) SND alone is adequate treatment for pN1 neck disease without adverse histological features. (R) Post-operative radiation for adverse histologic features following SND confers control rates comparable with more extensive procedures. (R) Adjuvant radiation following surgery for patients with adverse histological features improves regional control rates. (R) Post-operative chemoradiation improves regional control in patients with extracapsular spread and/or microscopically involved surgical margins. (R) Following chemoradiation therapy, complete responders who do not show evidence of active disease on co-registered positron emission tomography–computed tomography (PET–CT) scans performed at 10–12 weeks, do not need salvage neck dissection. (R) Salvage surgery should be considered for those with incomplete or equivocal response of nodal disease on PET–CT. (R)